FAKTOR YANG BERPENGARUH TERHADAP KELENGKAPAN IMUNISASI DASAR DI WILAYAH KERJA DINAS KESEHATAN KABUPATEN MOJOKERTO - Ridha Rahayu; Nurwidji; Dhonna Anggreni; Dwi Helynarti Syurandhari (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2025)
The immunization program is included in efforts to reduce morbidity, disability and mortality in infants and toddlers. The achievement of complete immunization still has not reached the target. A number of factors are known to influence the low coverage of complete basic immunization. This study aimed to determine the factors that influence the completeness of basic immunization in infants in the working area of the Mojokerto District Health Office. This study used a case control approach, with the population in this study were all mothers of infants in the Mojokerto District Health Office Work Area totaling 16,019 people. The sample in this study was 96 mothers of infants who had met the inclusion criteria. data were collected by questionnaire and then analyzed using logistic regression test. The results showed that there was an effect of mother's education level (p value = 0.000), mother's knowledge (p value = 0.000), and family support (p value = 0.000) on the completeness of basic immunization in infants in the working area of the Mojokerto District Health Office, and there was no effect of mother's employment status (p value = 0.285), number of children (p value = 0.885), and distance and affordability of immunization services (p value = 0.947) on the completeness of basic immunization in infants in the working area of the Mojokerto District Health Office. The positive effect of education level, knowledge and family support explains that the higher the education, the better the knowledge and family support, the higher the mother's motivation to immunize her child. Given the importance of the influence of family support on the completeness of immunization in infants, it is very important to involve the role of families in the toddler family development program so that families participate in supporting the implementation of immunization in infants.